2014
DOI: 10.1093/annonc/mdu364
|View full text |Cite
|
Sign up to set email alerts
|

Patients' preferences for subcutaneous trastuzumab versus conventional intravenous infusion for the adjuvant treatment of HER2-positive early breast cancer: final analysis of 488 patients in the international, randomized, two-cohort PrefHer study

Abstract: NCT01401166.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
115
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 132 publications
(132 citation statements)
references
References 9 publications
12
115
0
4
Order By: Relevance
“…There were less tangible benefits that were also not included in the analysis such as the patient's preference. As has been shown by the PrefHer study, if patients were given the choice, they would tend to prefer the SC formulation [20]. Although this was not assessed in this study, the convenience of SC could have impact on patients' satisfaction with the treatment and could increase treatment adherence.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…There were less tangible benefits that were also not included in the analysis such as the patient's preference. As has been shown by the PrefHer study, if patients were given the choice, they would tend to prefer the SC formulation [20]. Although this was not assessed in this study, the convenience of SC could have impact on patients' satisfaction with the treatment and could increase treatment adherence.…”
Section: Discussionmentioning
confidence: 86%
“…The efficacy of SC trastuzumab has been reported in the HannaH clinical trial which showed that the SC formulation was non-inferior and had a similar safety profile to the IV dosage form [16]. Additionally, the PrefHer study has reported patient preference for the SC administration for trastuzumab over IV, and that use of SC reduced the time of health care professionals and resources needed to manage patients [20]. This savings in time and cost relative to the IV formulation has been shown in several European studies [21]- [24].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In Cohort 1, 236 patients had their trastuzumab administered via a SID and in Cohort 2, 231 patients had SC delivery via a HHS. Results for both Cohorts 1 and 2 showed an overwhelming and strong preference for the SC route of administration [7,8]. The primary reasons for those (415/467; 89%) who preferred SC were that it saved time and resulted in less pain and discomfort.…”
Section: Introductionmentioning
confidence: 99%
“…В качестве наиболее важных причин выбора подкожной формы пациенты назвали экономию времени (80,3%) и уменьшение боли от манипуляции (34,3%). Опрос медицинского персонала показал: 77% предпочли подкожный путь введения, 3% -внутривенную форму и 20% не определились с предпо-чтениями относительно способа введения препарата [4].…”
unclassified